Serum Protein Biomarkers of Fibrosis Aid in Risk Stratification of Future Stricturing Complications in Pediatric Crohn's Disease. (May 2019) - Wu, Jing; Lubman, David M.; Kugathasan, Subra; Denson, Lee A.; Hyams, Jeffrey S.; Dubinsky, Marla C.; Griffiths, Anne M.; Baldassano, Robert N.; Noe, Joshua D.; Rabizadeh, Shervin; Gulati, Ajay S.; Rosh, Joel R.; et al.
Abstract : OBJECTIVES: Avoiding fibrostenotic complications is of paramount concern in the management of Crohn's disease (CD). We sought to investigate the association of candidate biomarkers of fibrosis collected at diagnosis with the future development of fibrostenotic CD. METHODS: Using the Risk Stratification and Identification of Immunogenetic and Microbial Markers of Rapid Disease Progression in Children with Crohn's Disease cohort, a multicenter prospective observational pediatric inception cohort, subjects with an inflammatory phenotype (B1) at diagnosis who later converted to a stricturing phenotype (B2) within 3 years were compared with those who remained B1. Serum collected at diagnosis underwent both parallel reaction monitoring–targeted proteomic analysis and conventional enzyme-linked immunosorbent assay for 10 candidate biomarkers of intestinal fibrosis. Cox proportional hazard regression was used for multivariable analysis of time-dependent outcomes. RESULTS: In 116 subjects 58 subjects with verified B1 phenotype at diagnosis who later converted to B2 disease were compared with 58 subjects who remained B1 over 3 years of follow-up. Extracellular matrix protein 1 (ECM1) levels in the upper quartile (hazard ratio [HR] 3.43, 95% confidence limit [CL] 1.33, 8.42) were associated with future fibrostenotic disease. ASCA IgA (HR 4.99, 95% CL 1.50, 16.68) and CBir levels (HR 5.19, 95% CL 1.83, 14.74) were also associated with future intestinal fibrostenosis, although ECM1 continued to demonstrate independent association with conversion to B2 even with adjustment for serologies in multivariable analysis (HR 5.33, 95% CL 1.29, 22.13). CONCLUSIONS: ECM1 and other biomarkers of fibrosis may aid in determining the risk of uncomplicated inflammatory disease converting to B2 stricturing phenotypes in children with CD. Prospective validation studies to verify test performance and optimize clinical utilization are needed before clinical implementation.